EFEKTIVITAS ZAKAT PRODUKTIF DALAM PENINGKATAN USAHA MUSTAHIK - Purnamasari, Lise; Ayuniyyah, Qurroh; Tanjung, Hendri (Kasaba, 2023)
The potential of zakat in Indonesia is very large if managed properly and correctly. The welfare of the poor will get a solution from the utilization of zakat funds. The productive zakat grant program is a way to distribute zakat funds to mustahik with the aim of providing additional business capital so that mustahiks can increase their business. Through this effort there is a transformation from mustahik to muzaki, or at least into munfik. This research aims to see the level of effectiveness of productive zakat in increasing mustahik business. This research took place at BAZNAS Bogor with 32 respondents.